2018
DOI: 10.1002/vms3.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of halothane on the electroencephalogram of the chicken

Abstract: Little is known about the effects of inhalant anaesthetics on the avian electroencephalogram (EEG). The effects of halothane on the avian EEG are of interest, as this agent has been widely used to study nociception and analgesia in mammals. The objective of this study was to characterize the effects of halothane anaesthesia on the EEG of the chicken. Twelve female Hyline Brown chickens aged 8–10 weeks were anaesthetized with halothane in oxygen. For each bird, anaesthesia was progressively increased from 1–1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Halothane-induced anaesthesia is used in the MAM to minimize the suppressive effect on EEG response that general anaesthesia can result in when induced by other agents, including isoflurane and methoxyflurane [18]. Halothane has been shown to minimise EEG suppression in rats [32] and chickens [33] whilst still allowing responses to be observed. Despite this, dampening EEG could still be a factor impacting results between conscious and anaesthetised lambs in the present study due to the nature of the anaesthetic agency.…”
Section: Discussionmentioning
confidence: 99%
“…Halothane-induced anaesthesia is used in the MAM to minimize the suppressive effect on EEG response that general anaesthesia can result in when induced by other agents, including isoflurane and methoxyflurane [18]. Halothane has been shown to minimise EEG suppression in rats [32] and chickens [33] whilst still allowing responses to be observed. Despite this, dampening EEG could still be a factor impacting results between conscious and anaesthetised lambs in the present study due to the nature of the anaesthetic agency.…”
Section: Discussionmentioning
confidence: 99%
“…Under isoflurane anesthesia, zebra finches ( Taeniopygia guttata ) exhibit high amplitude, low frequency slow waves similar in form to those occurring during natural SWS ( Beckers et al, 2014 ). In addition, brainwave patterns in isoflurane anesthetized zebra finches ( Beckers et al, 2014 ) and halothane anesthetized chickens ( Gallus gallus domesticus ) ( McIlhone et al, 2018 ) showed similar dose-dependent burst suppression patterns to those observed in anesthetized mammals. Finally, recordings from the hyperpallium of chickens anesthetized with urethane revealed periods of EEG slow waves, intermittently interrupted by periods of activation, which were associated with reduced neck muscle tone and heart rate, similar to the cyclic patterns observed in mammals, suggesting that urethane may be capable of inducing a similar REM sleep-like state in birds ( Shibata and Kadono, 1970 ).…”
Section: Introductionmentioning
confidence: 77%
“…The possibility that halothane anaesthesia blunted EEG responses to nociception in the present study cannot be discounted. However, this is unlikely, based on recent evidence indicating that halothane induces minimal EEG suppression in the chicken at concentrations of 1.5 MAC or lower [ 44 ]. In contrast, isoflurane and sevoflurane cause marked EEG suppression at 1–1.5 MAC and complete suppression at 2.0 MAC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%